Feminisms and Psychoanalysis of lacanian orientation. Notes for the hyphenation of knowledge. - Virgilí Pino, Dalia; Lazcano Vázquez, Claudia (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2020)
In the article we argue the need to promote a dialogue between Feminisms and Psychoanalysis of Lacanian Orientation. We debate on the relevance of this encounter as a condition of possibility for updating a clinic that transcends the pathologization of trans* experiences, psychiatric interventions and "corrective" treatments. The hyphenation is used as a theoretical-methodological option, that favors the production of hybrid knowledge. As a result, the favorable alliances are argued for the purpose of indicating some guidelines for a clinic of transsexuality as a psychiatric clinic capable of creating new fields of intelligibility.